Polemical Note: Can it Be Unethical to Provide Nutrition and Hydration to Patients with Advanced Dementia? (Diametros, 2016)
Patients suffering from advanced dementia present ethicists and caregivers with a difficult issue: we do not know how they feel or how they want to be treated, and they have no way of telling us. We do not know, therefore, whether we ought to prolong their lives by providing them with nutrition and hydration, or whether we should not provide them with food and water and let them die. Since providing food and water to patients is considered to be basic care that is morally required, it is usually only the provision of nutrition and hydration by artificial means that is considered to require ethical justification. Building on what I call a virtue-based conception of autonomy, I argue that, at least for some patients suffering from advanced dementia, even providing food and liquid by hand is morally wrong.